You are on page 1of 3

# Method of Variation of Parameters (Higher Order)

For higher order differential equations, we can use the method of variation of parameters to get a general solution. Steps for Solving Higher Order Nonhomogeneous Equations (Variation of Parameters): 1. Find the general solution to the corresponding homogeneous equation. 2. Find the particular solution to the nonhomogeneous equation by solving for v1(x), v2(x), ,vn(x), where the particular solution is given by y P ( x ) = v1 y1 + v 2 y 2 + ... + v n y n and the solutions of v1(x), v2(x), ,vn(x) are given by the following general formula:

vn =

g ( x )Wn ( x ) dx W [ y1 , y 2 ,..., y n ]( x )

Note: Recall that W[y1(x),y2(x),,yn(x)] is the Wronskian of y1(x), y2(x),,yn(x) given by:

y1 ( x ) y ' ( x) W [ y1 , y 2 ,..., y n ]( x ) = 1 M n 1 y1 ( x )
Note: The W n(x) in the formula is given by

y2 ( x) y2 ' ( x) M n 1 y2 ( x )

## ... yn ( x) ... y n ' ( x ) O M n 1 ... y n ( x )

Wn ( x ) = ( 1) n k W [ y1 ,... y k 1 , y k +1 ,..., y n ]( x ) ,
where n is the number of fundamental solutions u have and k = 1, 2, , n. 3. Write the general solution to the nonhomogeneous differential equation by adding the homogeneous solution to the particular solution to get the form y = y H + y P . Example: Find the general solution to the differential equation y" '+ y ' = tan x . 1. Find a general solution the associated homogeneous equation.

## r3 + r = 0 r ( r 2 + 1) = 0 r = 0, r = i --Thus, y H = c1 + c2 cos x + c3 sin x .

2. Find the particular solution to the nonhomogeneous equation. --We know that the fundamental solution is {y1,y2,y3} = {1, cos x, sin x}. Calculate the Wronskian of the fundamental set.

cos x

sin x

## W [1, cos x, sin x ] = 0 sin x cos x 0 cos x sin x

--Using cofactor expansion using the first column yields:

1 0

cos x sin x

sin x cos x = 1

sin x

cos x

0 cos x sin x

cos x sin x

cos x

sin x

cos x sin x

cos x

sin x

sin x cos x

= sin 2 x + cos 2 x = 1

## = cos 2 x + sin 2 x =1 W3 ( x ) = ( 1) 33W [1, cos x ]( x )

= ( 1) 3 = cos x 1 cos x 0 sin x

## = ( 1)( sin x ) = sin x

--Find v1(x), v2(x),and v3(x) by plugging into the formula above metioned in step 2.

v1 ( x ) = =

g ( x )W1 ( x ) dx W [ y1 ( x ), y 2 ( x ), y 3 ( x )]

v2 ( x) = =

1 = tan x + C

(tan x )(1)dx

g ( x )W2 ( x ) dx W [ y1 ( x ), y 2 ( x ), y 3 ( x )]

## (tan x )(sin x )dx

1

= (tan x sin x )dx sin x = sin x dx cos x sin 2 x = dx cos x 1 cos 2 = cos x x dx

= ln cos x + C
v3 ( x ) = = g ( x )W3 ( x ) dx W [ y1 ( x ), y 2 ( x ), y 3 ( x )]

## 1 cos 2 x = dx cos x cos x = (sec x cos x )dx = ln sec x + tan x sin x + C

--Thus

y P ( x ) = (1)(1) + (cos x )(ln sec x + tan x sin x + C 2 ) + (sin x )( cos x + C3 ) = 1 + (cos x )(ln sec x + tan x ) sin x cos x sin x cos x = 1 + (cos x )(ln sec x + tan x ) 2 sin x cos x = 1 + (cos x )(ln sec x + tan x ) sin 2 x
. Note: We took the constants to be zero to make the solution more feasible.

3. Write the general solution by adding together the homogeneous solution and the particular solution. Hence, the general solution is given by